Jamaican Food: History, Biology, Culture - Rashford, John (Ethnobiology Letters, 2010)
Review of Jamaican Food: History, Biology, Culture. B. W. Higman. 2008. University of West Indies Press, Jamaica. Pp. 580. 70.00 (cloth). ISBN (cloth) 9789766402051.